The Effect of COVID-19 Fear in the Postpartum Period on Mothers’ Obsessive–Compulsive Behaviors Related to Baby Care and Postpartum Depression - Kurt, Nuray; Battal, Sabriye; Koca, Hacer Ünver (AVES, 2023)
Objective: The study was conducted to evaluate the effect of fear of COVID-19 on mothers’ obses-sive–compulsive behaviors related to baby care and postpartum depression in the postpartum period. Methods: The descriptive study was conducted with a total of 211 mothers registered in the Family Health Centers of a province in eastern Turkey. The data of the study were collected with the Personal Information Form, the COVID-19 Fear Scale, the Scale of Obsessive and Compulsive Behaviors Related to Baby Care of Mothers in the Postpartum Period, and the Edinburgh Postpartum Depression Scale. Results: In the study, the frequency of postpartum depression in mothers was found to be 23.2%. We found a weak negative correlation between fear of COVID-19 in mothers’ obsessive–compul-sive behaviors related to infant care and a very weak positive correlation between postpartum depression (respectively r: ?.321, r: .199; p < .001, p < .05). Conclusion: In the study, it was determined that as the fear of COVID-19 experienced by mothers increased, obsessive–compulsive behaviors related to baby care decreased and the risk of postpartum depression increased. © 2023, AVES. All rights reserved.
Postpartum Dönemde COVID-19 Korkusunun Annelerin Bebek Bakımı ile İlgili Obsesif-Kompulsif Davranışlarına ve Postpartum Depresyona Etkisi
Keywords: COVID-19; midwifery; obsessive behavior; postpartum depression